The role of National Fatwa Committee in handling consumerism issues in Malaysia - Muhamad Miziazam, Yahya; Mohd Daud, Awang; Mansor, Sulaiman (Halal Products Research Institute, UPM, 2018)
The National Fatwa Committee (MFK) is a body responsible in issuing fatwa in Malaysia. It has an important role in determining a fatwa on certain issue whether it is permissible or not. Among the popular issue in the current community is consumerism issue. These include the permissibility of vaccine, swine DNA in food, consuming fish oil and other several significant consumerism issue. This study includes the process of fatwa production of these issues by MFK. It was also noted that the before a fatwa is produced, it will have to go through several processes before it is distributed to the public. The study also found that most of the fatwa was made by referring to al-Shafie school of taught. Despite that, there are other several methods in deriving laws based on maslahah, istihalah and other relevant fiqh methodology.